Comparative chromosomal mapping of microsatellite repeats reveals divergent patterns of accumulation in 12 Siluridae (Teleostei: Siluriformes) species - Ditcharoen, Sukhonthip (Genet Mol Biol, 2020)
The freshwater family Siluridae occurs in Eurasia and is especially speciose in South and Southeast Asia, representing an important aquaculture and fishery targets. However, despite the restricted cytogenetic data, a high diploid number variation (from 2n=40 to 92) characterizes this fish group. Considering the large genomic divergence among its species, silurid genomes have experienced an enormous diversification throughout their evolutionary history. Here, we aim to investigate the chromosomal distribution of several microsatellite repeats in 12 Siluridae species and infer about their possible roles in the karyotype evolution that occurred in this group. Our results indicate divergent patterns of microsatellite distribution and accumulation among the analyzed species. Indeed, they are especially present in significant chromosome locations, such as the centromeric and telomeric regions, precisely the ones associated with several kinds of chromosomal rearrangements. Our data provide pieces of evidence that repetitive DNAs played a direct role in fostering the chromosomal differentiation and biodiversity in this fish family.